The Viral Hepatitis Northern Network: A Platform for Addressing Viral Hepatitis in the Canadian North - Minuk, Gerald Y.; Osiowy, Carla; Sobol, Issac; Morse, John; Uhanova, Julia; Preiksaitis, Jutta Krista; R.P. Bryce Larke (Canadian Cryospheric Information Network, 2016)
An internet-based software program on Viral Hepatitis care in the North was developed, implemented, distributed, and is being regularly updated. The program allows healthcare providers to learn about HBV and diagnose/manage infected persons more effectively. The various forms of hepatitis B can be divided into more aggressive forms (subtypes B2-5) that frequently result in cirrhosis/liver cancer and more "benign" forms (subtypes B1 or B6) that rarely do so. Team members analyzed samples from Northern Canadians known to be infected with hepatitis B in the early 1980s. Representative sera from the 1983-85 serum bank were identified and transferred to the investigator's laboratory for testing for occult hepatitis B virus infection. The results revealed that the majority of Northern Canadians are infected with the more "benign" B6 subtype. Moreover, the amount of virus present in the circulation was relatively low, another predictor of a good outcome. The study also determined what percent of Northern Canadians are infected despite testing negative by standard diagnostic tests. Finally, the virus itself was analyzed to determine why in some instances it does not cause problems while in others, cirrhosis or liver cancer develop. The latter project was performed in conjunction with researchers from the United States and Denmark. Because HBV-induced rates of cirrhosis and liver cancer are higher in Alaska and Greenland than Northern Canada, collaborations were secured with investigators from these regions who submitted samples from infected individuals. The samples were used for genotyping, sequencing and identifying which HBV mutations are associated with adverse versus benign outcomes. : Purpose: Earlier studies have identified that approximately 3-5% of individuals residing in the Canadian North are infected with the hepatitis B virus (HBV). Based on data from similar populations elsewhere in the world, it was anticipated that untreated, 30-40% of these individuals will develop cirrhosis or liver cancer. One of the purposes of this project is to identify which of these individuals are at greatest risk of developing these life threatening clinical outcomes and establish a formal process whereby those at greatest risk could be monitored and treated to prevent such outcomes. In addition, the investigators intend to determine whether individuals who were previously infected with HBV but spontaneously (or as a result of anti-viral therapy) cleared the virus, remain at risk of developing cirrhosis and/or liver cancer. The main objectives of this proposal are 1) to establish a database for all hepatitis B infected Northern Canadians, 2) to identify which individuals are at greatest risk of developing cirrhosis and/or liver cancer from ongoing or previous hepatitis B viral infections and 3) determine why the virus causes disease in some but not all infected individuals. : Summary: Research has shown that 3-5% of individuals residing in the Canadian North are infected with hepatitis B virus (HBV) and likely, if left untreated, 30-40% will develop liver cancer. The aim of this project is to help identify HBV-infected Northern Canadians and to determine why some individuals develop liver cancer and others do not. An educational, computerized Viral Hepatitis database has been developed to help physicians and nurse practitioners in identifying, counselling and treating those infected with HBV. Laboratory data is captured in a Northern Canadian Viral Hepatitis Database to better understand the prevalence and characteristics of HBV across the North.